Hampered Vitamin B12 Metabolism in Gaucher Disease? - Luciana Hannibal PhD (Journal of Inborn Errors of Metabolism and Screening, 2017)
Untreated vitamin B 12 deficiency manifests clinically with hematological abnormalities and combined degeneration of the spinal cord and polyneuropathy and biochemically with elevated homocysteine (Hcy) and methylmalonic acid (MMA). Vitamin B 12 metabolism involves various cellular compartments including the lysosome, and a disruption in the lysosomal and endocytic pathways induces functional deficiency of this micronutrient. Gaucher disease (GD) is characterized by dysfunctional lysosomal metabolism brought about by mutations in the enzyme beta-glucocerebrosidase (Online Mendelian Inheritance in Man (OMIM): 606463; Enzyme Commission (EC) 3.2.1.45, gene: GBA1 ). In this study, we collected and examined available literature on the associations between GD, the second most prevalent lysosomal storage disorder in humans, and hampered vitamin B 12 metabolism. Results from independent cohorts of patients show elevated circulating holotranscobalamin without changes in vitamin B 12 levels in serum. Gaucher disease patients under enzyme replacement therapy present normal levels of Hcy and MMA. Although within the normal range, a significant increase in Hcy and MMA with normal serum vitamin B 12 was documented in treated GD patients with polyneuropathy versus treated GD patients without polyneuropathy. Thus, a functional deficiency of vitamin B 12 caused by disrupted lysosomal metabolism in GD is a plausible mechanism, contributing to the neurological form of the disorder but this awaits confirmation. Observational studies suggest that an assessment of vitamin B 12 status prior to the initiation of enzyme replacement therapy may shed light on the role of vitamin B 12 in the pathogenesis and progression of GD.